Lunang lunas reintegrating people into the society - De Jesus, Ramon Ivan Gregory D.; Araneta, Maureen Anne L. (Quezon City College of Architecture, University of the Philippines Diliman, 2017)
Lunang lunas is a self-sustaining halfway house with a museum and tourist information center located in Antipolo City. The facility seeks to rehabilitate drug abusers and equip them with skills and knowledge from them to be able to be integrated with their local communities after treatment. The facility will help maintain and restore the Hinulugang Taktak Falls as well as promote their local tourism.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman